Organization of the gene cluster for biosynthesis of penicillin in Penicillium nalgiovense and antibiotic production in cured dry sausages - Laich, F; Fierro, F; Cardoza, R.E; Martin, J.F (Applied and Environmental Microbiology, 1999)
Several fungal isolates obtained from two cured meat products from Spain were identified as Penicillium nalgiovense by their morphological features and by DNA fingerprinting. All P. nalgiovense isolates showed antibiotic activity in agar diffusion assays, and their penicillin production in liquid complex medium ranged from 6 to 38 microgram (.) ml(-1). We constructed a restriction map of the penicillin gene cluster of P. nalgiovense and found that the organization of the penicillin biosynthetic genes (pcbAB, pcbC, and penDE) is the same as in Penicillium chrysogenum and Aspergillus nidulans. The pcbAB gene is located in an orientation opposite that of the pcbC and penDE genes in all three species. Significant amounts of penicillin were found in situ in the casing and the outer layer of salami meat during early stages of the curing process, coinciding with fungal colonization, but no penicillin was detected in the cured salami. The antibiotic produced in situ was sensitive to penicillinase.